Absolute chronology of the Globular Amphora funeral complex at Malice, Sandomierz Upland - Witkowska, Barbara; Przybyła, Marcin M.; Podsiadło, Michał; Szczepanek, Anita; Włodarczak, Piotr (Baltic-Pontic Studies, 2021)
The article presents new radiocarbon datings made for a funeral complex from Malice, site 1, located on the Sandomierz Upland and related to the Globular Amphora culture. The complex included at least two human graves (features no. 32 and 33) and two animal deposits or sacrificial pits (no. 31 and probably 54). Feature 32 was a collective grave including five burials (of a male, a female and three children), while in Feature 33 the only one disarticulated human skeleton has been excavated. Pit 31 contained at least three animal individuals. It is possible the unexamined Pit 54 also contained animal depositions. The described features probably formed two clusters, each of which included a human grave and an accompanying pit with animal deposits. Altogether ten radiocarbon dates were obtained with the dated bone samples coming from five human skeletons found in Graves 32 and 33, and animal remains from Pit 31. The calibration results point to the first half of the 3rd millennium BC and stay between 2909 and 2472 BC (with the probability of 95.4%) or more precisely between 2898 and 2490 BC (probability of 68.2%). However, thanks to the stratigraphic documentation it was possible to determine that five deceased from Feature 32 were buried in three phases most likely to ca. 2850–2750 BC. It is highly probable that individual burials were separated by short time intervals. A similar age should be adopted for Feature 31 – a sacrificial pit linked to Grave 32. However, it is not possible to determine with any certainty the age of Grave 33: it could have been contemporaneous with, or slightly younger (ca 2620–2500 BC) than Feature 32.